Impact of Tourism Activity in Ciletuh-Palabuhanratu Geopark (CPG), Sukabumi, West Java - Aziza, Bella; Muntasib, E.K.S Harini; Hermawan, Rachmad (Media Konservasi, 2023)
Ciletuh-Palabuhanratu is designated by UNESCO as a geopark area and has become a tourist destination. Most of the use of Ciletuh is used for mass tourism, so research is carried out to determine the impact of tourism. This study aims to identify the impact of tourism activities on physical, biotic, socio-economic, and socio-cultural aspects in CPG. Interviews and field observations have been done to collect data at research sites and the determined comparison sites. Data were analyzed descriptively with qualitative and quantitative by comparing the results at the two study sites and the Mann Whitney Test to determine differences in community income. Tourism activities impact physical changes in water, soil compaction, landfill, temperature increase, and humidity decrease. Biotic impacts are changes in the composition of plant species, the composition of encounters of animal species with a decrease in the value of H '(1.4) and Dmg (4.2), and the destruction of wildlife. The socio-economic impact was identified from the availability of livelihoods, business opportunities, and increased income. Another impact is given opportunities for the public to contribute and opening access to technological and information developments.